ANALISIS UPAYA TANGKAP DAN POTENSI MAKSIMUM LESTARI IKAN TUNA MATA BESAR (Thunnus obesus) YANG DIDARATKAN DI PELABUHAN PERIKANAN SAMUDERA (PPS) KENDARI - Sulistiani Sulistiani; Andi Irwan Nur; Utama Kurnia Pangerang (Jurnal Perikanan Pantura (JPP), 2024)
The Banda Sea is part of the Indonesian Republic's Fisheries Management Area (WPPNRI) based on the Minister of Marine Affairs and Fisheries Regulation Number 1 of 2009 regarding the fisheries management area of the Republic of Indonesia. The purpose of this study is to analyze catch per unit effort (CPUE), and the results of sustainable catch potential (MSY) of bigeye tuna landed at the Kendari Oceanic Fishery Port (PPS). The data collected is derived from PPS Kendari over the past seven years (2016-2022). The research findings indicated that the catch effort value of bigeye tuna fluctuated from 2016 to 2022. There was an increase in 2017 with a value of 133 kg/trip, while in 2021, there was a decrease with a value of 32 kg/trip. The sustainable potential of bigeye tuna landed at PPS Kendari was assessed using the Fox model. The Fox model determined the optimum effort value (EMSY) to be 431 trips and the maximum catch value (CMSY) to be 42.174 kg/year. The stock status of bigeye tuna in the Banda Sea indicates overfishing.